IMPLEMENTASI BUDAYA MADRASAH DALAM PENINGKATAN KARAKTER RELIGIUS DI MTsN 13 JOMBANG - Ahmad Hamid Abdur Rozzaq; Nur ’Azah (JURNAL ILMIAH NUSANTARA, 2025)
Madrasah culture refers to the school environment where social and spiritual interactions occur among all school members within the framework of Islamic values, norms, and ethics. This culture serves as a crucial instrument in shaping the religious character of students. This study aims to describe: (1) How madrasah culture is planned to foster students’ religious character at MTsN 13 Jombang,(2) How it is implemented in daily educational practices, and (3) How the implementation is evaluated to ensure the development of students' religious values. Thisejresearcheisea field studyousing a qualitativefdescriptiveoapproach.lData werelcollectedfthroughlinterviews,lobservation,iandldocumentation. The datalanalysis techniques used includeldatafreduction,ldatakpresentation,fandkconclusionkdrawing. Tokensuremdatagvalidity,pthewresearcher employedwcredibility,mtransferability, idependability,kandoconfirmabilityktechniques. Thekresultstshowed thatothekplanning of madrasah culture was conducted through teachers' meetings, internal discussions, and the integration of programs into the academic calendar. The implementation involved routine activities such as istighasah, collective prayers, congregational shalat, the 5S movement (Smile, Greet, Salute, Polite, Courteous), morning handshakes with teachers, discipline enforcement, and character education strategies including role modeling, habituation, spontaneity, and reward-punishment systems. The evaluation process was carried out regularly by teachers, the student affairs deputy, and the head of the madrasah through daily monitoring and monthly reports. Overall, these programs were proven effective in fostering religious character traits such as discipline, politeness, responsibility, and a strong devotion to worship among students.